PENERAPAN TEKNIK LOAD BALANCING UNTUK PERANCANGAN JARINGAN VLAN PADA UNIT PENGELOLA SISTEM PENGENDALIAN LALU LINTAS DKI JAKARTA - Muhammad Gustriama; Sugiyono Sugiyono (STIKOM CKI, 2016)
Technology is one of the important aspects of life in today's global era. One of the technologies that are now growing rapidly is information technology. In the world of information technology, computer networks is essential for human life, both in institutions, educational, corporate, and others. One of the factors in a company that is very important is the level of speed and stability of the network structure in the sending and receiving of data, this is due to the increasing amount of data usage and support the performance and productivity that will be generated. So it should be able to maximize and optimize the width of the data path and the rate of speed of delivery. This will certainly streamline the time and productivity of the company as well as the process becomes stable and smooth work. In the process of this network structure, they often unstable and slow network in the delivery and reception of data, it is in value is not effective in the use and distribution of bandwidth. Thus making more bandwidth lines irregular and risk weakening the structure of the existing network. In this study, will be built a new network structure by using a type of network VLAN (Virtual Local Area Network) using PPDIOO and solutions to problems are conducted using techniques ECMP load balancing method on UPSPLL Jakarta. Expected results of the analysis and design of new network in Jakarta UPSPLL can help optimize the performance and stability of bandwidth.Keywords: Network, VLAN, Load Balancing, PPDIOO, ECMP